Three essays on fertility - Lim, Wee Pynn (2018)
This thesis consists of three essays on fertility. Essay one examines the relationship between the fluctuations in fertility and housing prices. In the overlapping generations (OLG) framework with fixed land supply, nonlinear dynamics can occur. As the preference for children increases, fluctuations in fertility rate and housing price become larger; lower preferences result in their convergence to steady state. The Singapore data show that the fluctuations in birth rates and housing resale prices are large in the earlier years compared to the later years. In addition, the estimates for birth rate are significant to resale housing price. Essay two explores the demand for housing with the demand for children under different social security systems in an OLG endogenous growth framework. Housing can be a socioeconomic good which takes up a substantial amount of one's income and competes with children for resources. It shows that for the same retirement income, the Pay-As-You-Go (PAYG) social security system results in high fertility compared to the fully funded (FF) system. Consumption for housing is also higher under the FF system. Unless the rate of return from the FF system is high enough, switching from the PAYG to the FF system tend to decrease fertility and increase growth. Essay three examines the determinants of fertility and identifies the theory that explains the decline in fertility in Singapore. Using the Autoregressive Distributive Lag (ARDL) model, results show that literacy rate and cost of living are the two variables that decrease fertility; estimates for private consumption and real GDP per capita are not significant for all model specifications. The Value of Children (VOC) approach offers the most plausible explanation for the decline in fertility in Singapore.